Effect of sleep on blood pressure among adults of urban slums: A Cross sectional study - Verma, Saurabh; Kumar, Arun; Gautam, Neelam; Mittal, Chhaya (Indian Journal of Community Health, 2024)
Introduction: Hypertension, the “Silent, Invisible killer” - is a modern day’s universal epidemic. The adult populations in slum area are more vulnerable for hypertension as they are so busy in the fulfilment of even day to day basic needs and care, family commitments and economic stress. Aim and objectives: To estimate the prevalence of hypertension among the adults (25-44 years) and to study the effect of sleep on blood pressure levels. Methodology: The present cross-sectional study was carried among adults aged between 25 to 44 years residing in the slums of Meerut District. 30 Cluster Sampling technique was used. The slum was selected as a cluster unit. During the visit by house-to-house survey, members of the family were listed and eligible person were interviewed and examined. Data collected on a structured and pretested questionnaire. Results: Prevalence of hypertension among those who had sleep duration of >8 hours per day was 44.8% followed by 20.1% and 17.5% among those who had 7-8 hours and less than 7 hours of sleep time respectively. It was found that 24.2% monophasic sleep pattern follower were hypertensives while the prevalence was 19.4% in biphasic pattern. Conclusion: Majority (55.4%) had a sleep duration between 7-8 hours, followed by 33.9% and 10.7% with <7 hours and >8 hours of sleep time respectively. Majority (61.3%) of the study population were having monophasic sleep pattern, while 36.3% were biphasic and 2.4% were multiphasic.